Outcomes of angioembolization and nephrectomy for renal angiomyolipoma associated with tuberous sclerosis complex: a real-world US national study. (4th May 2017) - Sun, Peter; Liu, Jamae; Charles, Hearns; Hulbert, John; Bissler, John
Abstract: Objective: To examine outcomes of clinical procedures for renal angiomyolipoma associated with tuberous sclerosis complex (TSC) based on US national health claims databases. Methods: This retrospective cohort study selected two cohorts of TSC patients, who underwent either embolization or nephrectomy (either partial or complete) for renal angiomyolipoma in the years from 2000 through 2011. Based on claims diagnosis codes, we estimated the prevalence rates of 10 angiomyolipoma-related conditions and 50 embolization- or nephrectomy-related conditions in the pre- and post-baseline periods respectively, and made cross-year and cross-period comparison of these rates with repeated measures analysis methods. Results: The embolization cohort ( N  = 4280) and the nephrectomy cohort ( N  = 3842) had mean baseline ages of 50.7 and 51.7 years with 52.5% and 51.3% males, respectively. After the intervention, the embolization cohort had statistically significant reductions (all p  < .05) in gross hematuria (−27.7%), retroperitoneal hemorrhage (−8.4%), and abdominal mass (−6.9%), and increases in hypertension (15.5%), renal mass or unspecified disorder of kidney and ureter (13.8%), anemia (5.1%), and renal insufficiency (3.3%). Similarly, the nephrectomy cohort saw statistically significant reductions (all p  < .05) in gross hematuria (−30.6%), flank pain (−7.5%), and abdominal mass (−6.4%), but increases in hypertension (11.9%), renal insufficiency (10.4%), and anemia (7.6%). Embolization was associated with post-procedure increases in renal mass or unspecified kidney/ureter disorder (13.9%), other disorders of kidney and ureter (3.4%), non-acute renal insufficiency (3.1%), flank pain (3.7%), renal insufficiency (3.2%), etc. (all p  < .05). Nephrectomy was associated with post-procedure increases in postoperative ileus (5.3%), pain and headache (4.8%), paralytic ileus (3.6%), etc. (all p  < .05). Conclusions: Both embolization and nephrectomy were effective, but associated with increases in certain angiomyolipoma-related conditions. Further, the embolization effect on gross hematuria, retroperitoneal hemorrhage, and abdominal mass might subside after the intervention year.